The Traditional Industry Sector in Algeria _Realities and Challenges - HARRAG , Masbah; BOUKALAA , Widad; NAMDILI , Bouchera (Milev Journal of Research and Studies, 2020)
Through this research paper, we seek to diagnose the reality of the traditional industrial sector in Algeria in order to identify the most important opportunities and challenges for this sector, As a vital sector that plays an important role in the diversification and modernization of the national economy, it is one of the most important alternatives available and possible to emerge from oil dependency, We have finally come to the conclusion that, despite the diversity and excellence of the products of traditional industry in Algeria, In addition to the efforts made by local authorities to promote the sector, it continues to suffer from a number of obstacles and challenges that hinder its promotion.